2016
DOI: 10.1016/j.cub.2015.12.046
|View full text |Cite
|
Sign up to set email alerts
|

Constrained Total Energy Expenditure and Metabolic Adaptation to Physical Activity in Adult Humans

Abstract: Summary Current obesity prevention strategies recommend increasing daily physical activity, assuming that increased activity will lead to corresponding increases in total energy expenditure and prevent or reverse energy imbalance and weight gain [1-3]. Such Additive total energy expenditure models are supported by exercise intervention and accelerometry studies reporting positive correlations between physical activity and total energy expenditure [4], but challenged by ecological studies in humans and other sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
280
7
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 242 publications
(314 citation statements)
references
References 34 publications
(51 reference statements)
16
280
7
11
Order By: Relevance
“…An explanation is the difference in exercise economy between subjects with a low PAI being untrained and subjects with a high PAI being trained. The training-induced increase in exercise economy limits the effect of an increase in physical activity on TEE and thus explains the curvilinear relation between physical activity and TEE as observed by Pontzer et al 37 In conclusion, maintenance metabolism is the largest component of TEE, especially at young and old age. Activity energy expenditure is the most variable component of TEE and can be increased when food intake allows.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…An explanation is the difference in exercise economy between subjects with a low PAI being untrained and subjects with a high PAI being trained. The training-induced increase in exercise economy limits the effect of an increase in physical activity on TEE and thus explains the curvilinear relation between physical activity and TEE as observed by Pontzer et al 37 In conclusion, maintenance metabolism is the largest component of TEE, especially at young and old age. Activity energy expenditure is the most variable component of TEE and can be increased when food intake allows.…”
Section: Discussionmentioning
confidence: 55%
“…Pontzer et al 37 concluded, from a comparative analysis of TEE and physical activity data, TEE increases with physical activity al low activity levels but plateaus with higher activity levels. They suggested a model of constrained TEE with metabolic adaptations to physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Ultramarathons, defined as races lasting over 4 hours (Knez, Coombes, & Jenkins, 2006) (but often several days in length). Recent work suggests that high levels of energy expenditure cause metabolic adaptation to reduce total energy output (Pontzer et al, 2016), and the high energetic costs of locomotion necessitated by ultramarathons are expected to necessitate physiological trade‐offs. This is due to energy deficit induced by a combination of the high levels of energy expenditure in physiological systems linked to locomotion, and the lack of opportunity to ingest any significant meals (Knechtle & Bircher, 2005; Knechtle, Enggist, & Jehle, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Other surveys have also shown lower performance of women in relation to physical fitness indicators 5,8 . During systematic (regular) physical activity, physiological adaptations such as cardiac hypertrophy and increase in the number of oxygen and organic transporters, such as increased muscle recruitment, increased joint mobilization and increased energy expenditure are generated, and the lower involvement in physical activity of girls (18.8%) compared to boys (27.6%) in the present study (data not shown) could imply lower magnitude of these adaptations, reflecting worse prognoses regarding aerobic fitness, muscular strength, flexibility and body fat 29 .…”
Section: Discussionmentioning
confidence: 57%
“…The long period in front of the screen is associated with increased caloric intake and excess body fat 23 , which in turn is directly related to lower maximum oxygen consumption and low aerobic fitness levels 30 . In addition, body immobility resulting from high sitting periods is considered a stressor for the organism 14 , which may contribute to a decrease in muscular strength levels and flexibility 29 .…”
Section: Discussionmentioning
confidence: 99%